1995
DOI: 10.4269/ajtmh.1995.53.167
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Side Effects of Praziquantel in an Epidemic Focus of Schistosoma mansoni

Abstract: keywords Schistosoma mansoni, praziquantel, resistance correspondence Y.S. Liang, Jiangsu Institute of Parasitic Diseases, Meiyuan, Wuxi, Jiangsu 214064, P. R.China.The tolerance of Schistosoma mansoni to praziquantel has been reported in some endemic regions (Fallon et al. 1995;Stelma et al. 1995;Ismail et al. 1996;Guisse et al. 1997). To establish the reasons for clinical failures of praziquantel, a simple, quick and economic assay is required to detect resistance. Ideally this will involve the use of eggs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
157
3
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(172 citation statements)
references
References 5 publications
9
157
3
3
Order By: Relevance
“…These values are in general within the usual cure rate ranges (63-95%) of PZQ against S. mansoni reported in different epidemiological settings [4,[26][27][28] . Some previous studies have reported efficacy higher than 85% for PZQ [29][30][31][32][33][34] , while others have reported lower (<63%) efficacy for the drug [13][14][15][16][17][18][19][20][21]35,36] . Such variations might be attributable to differences in the number of treatment, factors related to the host, parasite, and drugs or to the methodology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These values are in general within the usual cure rate ranges (63-95%) of PZQ against S. mansoni reported in different epidemiological settings [4,[26][27][28] . Some previous studies have reported efficacy higher than 85% for PZQ [29][30][31][32][33][34] , while others have reported lower (<63%) efficacy for the drug [13][14][15][16][17][18][19][20][21]35,36] . Such variations might be attributable to differences in the number of treatment, factors related to the host, parasite, and drugs or to the methodology.…”
Section: Discussionmentioning
confidence: 99%
“…Asian Pacific Journal of Tropical Biomedicine journal homepage:www.elsevier.com/locate/apjtb efficacy [13][14][15][16][17][18][19][20][21] . In addition, the expiry of patent protection for the major anthelminthic drugs [10,22] and international competition that has substantially reduced the price of the drug [23] have made several low-cost brands and generic formats of PZQ available on the market.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports of treatment failure in Senegal and Egypt [6,7], where isolates with reduced susceptibility to Praziquantel were obtained, have raised concerns about development of drug resistance. Further in vitro experiments confirmed the development of parasite resistance to Praziquantel compared with susceptible isolates [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…At present, praziquantel (PZQ) is the drug of choice for the treatment of all forms of schistosomiasis 3 . However, dependence on a single drug is a concern because of the possible development of resistance in some strains 4,5 . A second drug, oxamniquine (OXA), acts against Schistosoma mansoni, which is found in Africa, and against Schistosoma haematobium in South America, where it is the only species of this genus present.…”
Section: Introductionmentioning
confidence: 99%